Assessment of the Social-Economic Contributions of Mgahinga National Park to Local Communities in Muramba Sub-County, Kisoro District, South-Western Uganda. - Mahoro, Shallon (Kabale University, 2023)
National parks like Mgahinga National Park contribute various socio-economic goods and services to the local communities around them and therefore contribute to improvement of livelihoods. Parks do not only provide food, medicine, fodder, fuel wood, and poles to local communities but also parks offer job opportunities, educative programs, and other community services to local people. The purpose of this study was therefore assessment of the social-economic contributions of Mgahinga National Park to local communities in Muramba sub-county, Kisoro District. The study was guided by the specific objectives which include investigating the contributions of Mgahinga National Park to the development of local communities, establishing the challenges faced by people living near Mgahinga National Park, and assessing the possible solutions to the challenges faced by communities near Mgahinga National Park in Muramba sub-county, Kisoro District. The study employed descriptive cross-sectional survey design utilizing both qualitative and quantitative data collection and analyses methods. Using simple random and purposive sampling techniques, a total of 109 respondents were selected to participate in the study. Questionnaires, observation and interviewing methods of data collection were used in the study. The social-economic contributions of the National Parks to the development of local communities were provision of employment opportunity, poverty reduction, carbon sequestration, water catchment areas, rainfall formation, community development and management of related land use activities. The challenges faced by people living near the National Parks were limited livelihood alternatives, increased competition on other development initiatives, inadequate innovation and human capital, crop animal raiding, prostitution and lack of mass education on conservation.The possible solutions to the challenges faced by communities near Mgahinga National park were community`s involvement in conservation activities, community-based natural resource management, ensuring environmental sustainability, practical field-based monitoring of illegal activities, use of wildlife friendly products and implementation of policies. Based on the findings of this study, it was recommended that there should be mass education on conservation to local communities in Muramba sub-county Kisoro district to ease conservation. The local residents should be trained on sustainable land management activities and better farming methods to ease conservation.